2008
DOI: 10.1055/s-0039-1697351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Curing Method and Exposure Time on Mechanical Properties of Resin Based Dental Materials

Abstract: Objectives The aim of this study was to investigate microhardness and compressive strength of composite resin (Tetric-Ceram, Ivoclar Vivadent), compomer (Compoglass, Ivoclar, Vivadent), and resin modified glass ionomer cement (Fuji II LC, GC Corp) polymerized using halogen light (Optilux 501, Demetron, Kerr) and LED (Bluephase C5, Ivoclar Vivadent) for different curing times. Methods Samples were placed in disc shaped plastic molds with uniform size of 5 mm diameter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 18 publications
2
32
0
4
Order By: Relevance
“…Additionally, self-curing mechanisms were employed for the five cement compositions to subject the investigative materials to the same experimental conditions, but RMGIC cements are typically light-cured in the clinic, a process which significantly expedites the cement setting time. 49 Lastly, the inherent variability in the specified specimen preparation protocol for ZOE and ZP cement compositions, both of which are powder-liquid formulations, can lead to undesired alterations in material properties. For example, the manufacturer's instructions for ZOE and ZP cement permit the user to incorporate additional liquid monomer to achieve a desired consistency, but the increased liquid concentration (e.g., eugenol) will lead to increased monomer leaching and subsequent cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, self-curing mechanisms were employed for the five cement compositions to subject the investigative materials to the same experimental conditions, but RMGIC cements are typically light-cured in the clinic, a process which significantly expedites the cement setting time. 49 Lastly, the inherent variability in the specified specimen preparation protocol for ZOE and ZP cement compositions, both of which are powder-liquid formulations, can lead to undesired alterations in material properties. For example, the manufacturer's instructions for ZOE and ZP cement permit the user to incorporate additional liquid monomer to achieve a desired consistency, but the increased liquid concentration (e.g., eugenol) will lead to increased monomer leaching and subsequent cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…23 Two other phenomena connected with the polymerization of the resins are volumetric shrinkage and heating. 24 The adequacy of the polymerization is influenced by many factors such as the distance of the light source from the resin; the type of resin (shade, translucency and thickness, viscosity); 25 the temperature; the curing and post-irradiation time; 24,26 the reactivity of the monomer; the types and amounts of inhibitors, the light; the oxygen permeability 27 and also the type and amount of photo initiator/co-initiator systems. 13,28 It has also been shown that dynamic heating of the resin samples increases the rate of polymerization resulting in higher conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate polymerization of dental resins depends also on the intensity of the light source (power density measured in mW/cm²), correct Cotti, Scungio, Dettori, Ennas wavelength of the light and duration of the exposure. 25,26 If these parameters are not adequate an incomplete polymerization will occur, together with the exhibition of poor physical properties of the material, higher solubility and consequently an early failure. 31 In our experiment we used Ul-traLume LED 5 and Mini LED.…”
Section: Discussionmentioning
confidence: 99%
“…The material was covered with another celluloid strip, and the glass slide weighed of 200 g for 1 minute until the slide touched the mold completely, thus allowing excess composite to flow prior to curing. [18][19][20] Next, the excess restorative material was removed. The tested restorative material was light cured for 20 seconds on each side using a light-curing unit QHL75 (505 mW/cm 2 ) (Dentsply, York, PA, USA).…”
Section: Specimen Preparationmentioning
confidence: 99%